Genetic deletion of platelet PAR4 results in reduced thrombosis and impaired hemostatic plug stability. (10th November 2021) - Lee, Robert H.; Kawano, Tomohiro; Grover, Steven P.; Bharathi, Vanthana; Martinez, David; Cowley, Dale O.; Mackman, Nigel; Bergmeier, Wolfgang; Antoniak, Silvio
Abstract: Background: Protease‐activated receptor 4 (PAR4) is expressed by a wide variety of cells, including megakaryocytes/platelets, immune cells, cardiomyocytes, and lung epithelial cells. It is the only functional thrombin receptor on murine platelets. A global deficiency of PAR4 is associated with impaired hemostasis and reduced thrombosis. Objective: We aimed to generate a mouse line with a megakaryocyte/platelet‐specific deletion of PAR4 (PAR4 fl/fl ;PF4 Cre+ ) and use the mouse line to investigate the role of platelet PAR4 in hemostasis and thrombosis in mice. Methods: Platelets from PAR4 fl/fl ;PF4 Cre+ were characterized in vitro . Arterial and venous thrombosis was analyzed. Hemostatic plug formation was analyzed using a saphenous vein laser injury model in mice with global or megakaryocyte/platelet‐specific deletion of PAR4 or wild‐type mice treated with thrombin or glycoprotein VI (GPVI) inhibitors. Results: PAR4 fl/fl ;PF4 Cre+ platelets were unresponsive to thrombin or specific PAR4 stimulation but not to other agonists. PAR4 −/− and PAR4 fl/fl ;PF4 Cre+ mice both exhibited a similar reduction in arterial thrombosis compared to their respective controls. More importantly, we show for the first time that platelet PAR4 is critical for venous thrombosis in mice. In addition, PAR4 −/− mice and PAR4 fl/fl ;PF4 Cre+ mice exhibited a similar impairment in hemostatic plug stability in a saphenous vein laser injury model. Inhibition of thrombin in wild‐type mice gave a similar phenotype. Combined PAR4 deficiency on platelets with GPVI inhibition did not impair hemostatic plug formation but further reduced plug stability. Conclusion: We generated a novel PAR4 fl/fl ;PF4 Cre+ mouse line. We used this mouse line to show that PAR4 signaling in platelets is critical for arterial and venous thrombosis and hemostatic plug stability.